Pengaruh Budaya Organisasi Terhadap Kepuasan Kerja Karyawan pada Lembaga Keuangan Syariah Baitul Maal Wat Tamwil - Hamidah, Siti; Troena, Eka Afnan; Suman, Agus (TEMA, 2001)
Based on functions of organizational culture this study was run with Syariâ€™ah Finance Institution Baitul Maal wat Tamwil which has â€œIsÂlamicâ€ feature. This study was aimed at finding out the effect of organizational culture on staffs job satisfaction and to describe the biggest organizational culture factor which contributes to staffs job satisfaction. The extraction of 13 syariâ€™ah organizational culture variables results in 3 factors: (1) organizational assumption of the nature of human and human actiinty; (2) the organization's relationship with its environment; and (3) the organizational assumption of the nature of reality and truth. These factors significantly show positive effect to staffs job satisfaction, both simultanously and partially, and the bigÂgest effect to staffâ€™s job satisfaction was given by second factor. ReÂlationship with the environment extremely affected by national (local) culture where was study conducted explains the phenomenon hapÂpened. Katakunci: Budaya Organisasi, Kepuasan Kerja, Lembaga Keuangan Syariah, Baitul Maal Wattamwil